2017
DOI: 10.1090/mcom/3256
|View full text |Cite
|
Sign up to set email alerts
|

An inverse theorem for compact Lipschitz regions in ℝ^{𝕕} using localized kernel bases

Abstract: While inverse estimates in the context of radial basis function approximation on boundary-free domains have been known for at least ten years, such theorems for the more important and difficult setting of bounded domains have been notably absent. This article develops inverse estimates for finite dimensional spaces arising in radial basis function approximation and meshless methods. The inverse estimates we consider control Sobolev norms of linear combinations of a localized basis by the Lp norm over a bounded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
(51 reference statements)
0
27
0
Order By: Relevance
“…The optimal stencils decay extremely quickly away from the origin. This is predicted by results of [19] concerning exponential decay of Lagrangians of polyharmonic kernels, as used successfully in [13] to derive local inverse estimates. See [24] for an early reference on polyharmonic near-Lagrange functions.…”
Section: Examplesmentioning
confidence: 69%
“…The optimal stencils decay extremely quickly away from the origin. This is predicted by results of [19] concerning exponential decay of Lagrangians of polyharmonic kernels, as used successfully in [13] to derive local inverse estimates. See [24] for an early reference on polyharmonic near-Lagrange functions.…”
Section: Examplesmentioning
confidence: 69%
“…We use the notation u β,Z,Φm := zj ∈Z β j Φ m (· − z j ) to denote the functions in the trial space U Z,Φm spanned by translates of the kernel Φ m on the trial centers in Z with coefficients forming a vector β ∈ R |Z| . Then (I − ∆) ν u β,Z,Φm = u β,Z,Ψm−ν holds, and these are the functions that we use in [13,Eqn. 3.19].…”
Section: Assumption 21 (Smoothness Of Domain and Solution)mentioning
confidence: 99%
“…Meshless methods also allow for flexibility in the selection of approximating functions, in particular non-polynomial approximating functions. In this paper the approximating spaces will be spanned by certain localized kernel bases [10,13] that are distinguished by a rigorous approximation theory and give rise to very practical and efficient numerical methods.…”
Section: Introductionmentioning
confidence: 99%
“…The numerical analysis provided in this paper will be based on two specific classes of local Lagrange functions that will play the role of bases for the spaces U h and Λ h appearing in (2.6). In [13], it was shown that for either thin-plate splines or Matérn kernels on R n , local Lagrange functions with each function determined by O(log N ) n points contained in a ball of radius Kh log h centered at a given point ξ have very rapid decay around ξ. Moreover such functions generate very stable bases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation